Homeschooling in the Digital Age: The Role of Technology in Supporting Home Education - Sonia Natalia; Nurpadilah Nurpadilah; Gusmaneli Gusmaneli (Educare: Journal Educational and Multimedia, 2024)
This research discusses the use of technology in homeschooling and its impact on children’s learning processes. By adopting a literature review approach, we identify, evaluate, and synthesize current research findings related to technology-based homeschooling. This study outlines the benefits of technology as a source of information and a learning tool, as well as the challenges faced in its implementation, such as accessibility, parental technology skills, and data security. Additionally, we investigate the social and emotional impacts experienced by homeschooling students who utilize technology in their learning. Through a combination of systematic literature review and traditional review, this research aims to provide deeper insights into the potentials and challenges within homeschooling education, as well as recommendations for developing more effective homeschooling practices in the future.